2016
DOI: 10.1111/odi.12568
|View full text |Cite
|
Sign up to set email alerts
|

Tooth agenesis in osteogenesis imperfecta related to mutations in the collagen type I genes

Abstract: The prevalence of tooth agenesis is high (17%) in individuals with OI, and OI caused by a qualitative collagen I mutation is associated with oligodontia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 43 publications
1
47
1
Order By: Relevance
“…We previously reported a high prevalence of hypodontia (11%) and oligodontia (6%) in children and adolescents with OI [17]. In the present cohort, we observed a hypodontia prevalence of 9%, which is only slightly higher than reported prevalences of 6−8% for the Nordic population in general [18–20].…”
Section: Discussioncontrasting
confidence: 69%
“…We previously reported a high prevalence of hypodontia (11%) and oligodontia (6%) in children and adolescents with OI [17]. In the present cohort, we observed a hypodontia prevalence of 9%, which is only slightly higher than reported prevalences of 6−8% for the Nordic population in general [18–20].…”
Section: Discussioncontrasting
confidence: 69%
“…Craniofacial and dentoalveolar abnormalities are present in mild, moderate, and severe types of OI. Cephalometric studies have revealed that dentoalveolar structures and the condylar processes are often vertically underdeveloped in OI types III and IV . Clinically, the hypoplastic maxilla and reduced vertical and transverse dimensions result in a malocclusion, such as bilateral open bite or cross bite, and counterclockwise (overclosing) rotation of the mandible .…”
Section: Introductionmentioning
confidence: 99%
“…Cephalometric studies have revealed that dentoalveolar structures and the condylar processes are often vertically underdeveloped in OI types III and IV. (6)(7)(8)(9) Clinically, the hypoplastic maxilla and reduced vertical and transverse dimensions result in a malocclusion, such as bilateral open bite or cross bite, and counterclockwise (overclosing) rotation of the mandible. (9) The facial appearance of moderate and severe OI is often characterized by frontal bossing, triangular face shape, (3) and macrocephaly.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported a high prevalence of hypodontia and oligodontia in adolescents with OI [17]. Apically extended pulp chambers (taurodontism), primary retained permanent second molars, (failure of eruption before emergence, without a physical barrier in the eruption path) [12, 18] and aberrant craniofacial development with a retrognathic maxilla often occur in patients with OI [19, 20].…”
Section: Introductionmentioning
confidence: 99%